Design of Metamaterial Based Efficient Wireless Power Transfer System Utilizing Antenna Topology for Wearable Devices - Tarakeswar Shaw; Gopinath Samanta; Debasis Mitra; Bappaditya Mandal; Robin Augustine (Sensors, 2021)
In this article, the design of an efficient wireless power transfer (WPT) system using antenna-based topology for the applications in wearable devices is presented. To implement the wearable WPT system, a simple circular patch antenna is initially designed on a flexible felt substrate by placing over a three-layer human tissue model to utilize as a receiving element. Meanwhile, a high gain circular patch antenna is also designed in the air environment to use as a transmitter for designing the wearable WPT link. The proposed WPT system is built to operate at the industrial, scientific and medical (ISM) band of 2.40–2.48 GHz. In addition, to improve the power transfer efficiency (PTE) of the system, a metamaterial (MTM) slab built with an array combination of 3 × 3 unit cells has been employed. Further, the performance analysis of the MTM integrated system is performed on the different portions of the human body like hand, head and torso model to present the versatile applicability of the system. Moreover, analysis of the specific absorption rate (SAR) has been performed in different wearable scenarios to show the effect on the human body under the standard recommended limits. Regarding the practical application issues, the performance stability analysis of the proposed system due to the misalignment and flexibility of the Rx antenna is executed. Finally, the prototypes are fabricated and experimental validation is performed on several realistic wearable platforms like three-layer pork tissue slab, human hand, head and body. The simulated and measured result confirms that by using the MTM slab, a significant amount of the PTE improvement is obtained from the proposed system.